Guidelines and Resources for Prescribing Load using Velocity Based Training - Joseph Moore; Harry Dorrell (International Universities Strength and Conditioning Association, 2020)
Different relative loads during resistance training movements are considered to result in varying physiological adaptions. The challenge facing coaches and athletes is how to determine what absolute load relates to the prescribed relative load and how to account for changes in strength. Velocity based training may offer a solution to this problem. Currently there are limited guidelines for coaches to follow and the proposed methods are associated with increased burden. Therefore, this article provides simple evidence based guidelines and an online application to support the use of velocity based training as a method of auto-regulation during resistance training.